Complementary expression of EphA7 and SCO-spondin during posterior commissure development - Stanic, Karen; Vera, América; González, Melissa; Recabal, Antonia; Astuya, Allison; Torrejón, Marcela; Montecinos, Hernán; Caprile, Teresa (Frontiers in Neuroanatomy, 2014)
Bilaterally symmetric organisms need to exchange information between the two sides of their bodies in order to integrate sensory inputs and coordinate motor control. This exchange occurs through commissures formed by neurons that project axons across the midline to the contralateral side of the central nervous system. The posterior commissure is the first transversal axonal tract of the embryonic vertebrate brain. It is located in the dorsal portion of the prosomere 1, at the caudal diencephalon. The axons of the posterior commissure principally come from neurons of ventrolateral and dorsolateral pretectal nuclei (parvocellular and magnocellular nucleus of the posterior commissure, respectively) that extend their axons toward the dorsal region. The trajectory of these axons can be divided into the following three stages: 1) dorsal axon extension towards the lateral roof plate; 2) fasciculation in the lateral roof plate; and 3) midline decision of turning to the ipsilateral side or continuing to the opposite side. The mechanisms and molecules that guide the axons during these steps are unknown. In the present work, immunohistochemical and in situ hybridization analyses were performed, with results suggesting the participation of EphA7 in guiding axons from the ventral to the dorsal region of the prosomere 1 through the generation of an axonal corridor limited by repulsive EphA7 walls. At the lateral roof plate, the axons became fasciculated in presence of SCO-spondin until reaching the midline. Finally, EphA7 expression was observed in the diencephalic midline roof plate, specifically in the region where some axons turn to the ipsilateral side, suggesting its participation in this decision. In summary, the present work proposes a mechanism of posterior commissure formation orchestrated by the complementary expression of the axon guidance cues SCO-spondin and EphA7.